CONTRIBUTION OF SELF-REGULATED LEARNING AND INTEREST IN LEARNING TO THE ACADEMIC SUCCESS OF ARCHIVES MANAGEMENT IN PUBLIC VOCATIONAL SCHOOLS - Safhira, Nur; Sumiati, Ati; Faslah, Roni (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The aim of this research is to describe the effect of self-regulated learning and learning interest in student learning outcomes. This research was conducted at Public Vocational High Schools 10 Jakarta in the early year 2023/2024 with a population of class X and XI majoring in Office Management and Business Services (MPLB) of 144 students. The sample used in this research consisted of 106 students using proportional random sampling techniques. The Learning Outcome variable data uses secondary data, while the Self-Regulated Learning and Learning Interest variable data uses primary data using a Likert scale model. The analysis technique for this research consists of instrumental tests (validity and reliability), analysis prerequisite tests (normality and linearity tests), classical assumption tests (multicollinearity and heteroscedasticity), and Multiple Regression Analysis (simultaneous F test, partial T test and coefficient of determination). The results of this study indicate that there is a significant influence between self-regulation learning and learning outcomes, learning interest influences learning outcomes, and self-regulated learning and learning interest both influence learning outcomes simultaneously.